Schuurs‐Hoeijmakers syndrome in a patient from India. Issue 4 (28th January 2019) - Dutta, Atanu Kumar
Abstract : Schuurs‐Hoeijmakers syndrome (SHMS), or Autosomal Dominant Mental Retardation Syndrome type 17 (MRD17) is a rare form of intellectual disability with distinct facial features. A recurrent de novo heterozygous c.607C>T, p.Arg203Trp mutation in the PACS1 gene accounts for all reported cases except for one patient with a de novo heterozygous c.608G>A, p.Arg203Trp mutation. Ethnic background is known to affect the clinical manifestation of dysmorphic syndromes. Here we describe the first Indian patient with Schuurs‐Hoeijmakers syndrome (SHMS) with a de novo heterozygous NM_018026.3 ( PACS1 ):c.607C>T (p.Arg203Trp) variant. He is the only child with SHMS with a cleft lip. Thus our report expands the phenotypic spectrum of SHMS and establishes its occurrence across populations.